Evaluation of suitable DNA regions for molecular identification of high value medicinal plants in genus Kaempferia - Maslin Osathanunkul (2018)
© 2017 Taylor & Francis Group, LLC. DNA barcoding coupled high resolution melting (Bar-HRM) is an emerging method for species discrimination based on DNA dissociation kinetics. The aim of this work was to evaluate the suitability of different primer sets, derived from selected DNA regions, for Bar-HRM analysis of species in Kaempferia (Zingiberaceae). Four primer pairs were evaluated (rbcL, rpoC, trnL and ITS1). It was observed that the ITS1 barcode was the most useful DNA barcoding region overall for species discrimination out of all of the regions and primers assessed. Thus, the primer pair derived from the ITS1 region was the single most effective region for the identification of the tested species, whereas the rbcL primer pair gave the lowest resolution. Our Bar-HRM developed here would not only be useful for identification of Kaempferia plant specimens lacking essential parts for morphological identification but will be useful for authenticating products in powdered form of a high value medicinal species Kaempferia parviflora, in particular.